Structural response of simple partially-clad steel frames to long-duration blast loading. (August 2021) - Cannon, Laura; Clubley, Simon K.
Abstract: Typically defined as having a positive phase duration in excess of 100 ms, long duration blast events generate significant impulse and dynamic pressures fundamentally exerting damaging drag loads on steel frames. Large scale blast waves have the capability to completely engulf entire buildings resulting in considerable damage to a multitude of structural members. Most literature investigating steel structural response to long duration events considers only isolated column elements, which neglects frame interaction effects. Isolated column response is dependent upon applied blast pressures and section strength, both of which vary with orientation. Isolated column studies often assume cladding is removed instantly upon blast wave arrival. Despite current guidelines, some systems are not frangible or designed to break away instantly resulting in an undesirable partial cladding removal that can increase load on critical elements. Importantly this study investigates the structural response of two partially-clad simple steel frames to long duration blast at two angles of orientation. Results are compared to understand the effect on frame response and correlated with equivalent isolated column damage to determine the effects of frame interaction and partial cladding removal.